2012
DOI: 10.1213/ane.0b013e31824ea491
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Wastage in Anesthesia

Abstract: Propofol does not degrade in nature, accumulates in body fat, and is toxic to aquatic life. We reduced wastage by removing 50 and 100 mL vials of propofol from the pharmacy, retaining only the smallest size (20 mL).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
85
1
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(122 citation statements)
references
References 8 publications
2
85
1
12
Order By: Relevance
“…In previous studies [71,72], wasting of propofol, other injectable drugs, and controlled substances (CS) was generally higher (4.1%) at the same facilities as reported herein. For example; Mankes [71] found that 41 liters of propofol emulsion and other liquid injectable surgical drugs were wasted of 150 liters dispensed.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…In previous studies [71,72], wasting of propofol, other injectable drugs, and controlled substances (CS) was generally higher (4.1%) at the same facilities as reported herein. For example; Mankes [71] found that 41 liters of propofol emulsion and other liquid injectable surgical drugs were wasted of 150 liters dispensed.…”
Section: Discussionsupporting
confidence: 69%
“…Sim et al [16] assayed twenty-four (24) different drugs in Korean wastewater finding ug/L levels of pharmaceuticals in hospital effluent. Olivera et al [71] measured 185 pharmaceutical and personal care products by liquid chromatographymass spectroscopy (LC-MS) in hospital effluent and wastewater in Suffolk County, USA finding very low levels ranging from undetectable (most) to 1.4 ug/L for erythromycin.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations